2018
DOI: 10.1128/aem.02137-17
|View full text |Cite
|
Sign up to set email alerts
|

Nutrient-Colimited Trichodesmium as a Nitrogen Source or Sink in a Future Ocean

Abstract: Nitrogen-fixing (N) cyanobacteria provide bioavailable nitrogen to vast ocean regions but are in turn limited by iron (Fe) and/or phosphorus (P), which may force them to employ alternative nitrogen acquisition strategies. The adaptive responses of nitrogen-fixers to global-change drivers under nutrient-limited conditions could profoundly alter the current ocean nitrogen and carbon cycles. Here, we show that the globally-important N-fixer fundamentally shifts nitrogen metabolism towards organic-nitrogen scaveng… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
39
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 30 publications
(41 citation statements)
references
References 56 publications
2
39
0
Order By: Relevance
“…Recently, the microbial communities and potential denitrification activities associated with Trichodesmium have attracted much attention in the research community ( 32 , 33 ). The presence of potentially denitrifying microorganisms associated with Trichodesmium has raised the hypothesis that Trichodesmium may even support denitrification in its O 2 microenvironment ( 34 ), as recently demonstrated experimentally in N 2 -fixing Nodularia colonies ( 21 ). In the latter study, it was shown that a complete aerobic and anaerobic N cycle can be present in the microenvironment of Nodularia colonies.…”
Section: Discussionmentioning
confidence: 97%
“…Recently, the microbial communities and potential denitrification activities associated with Trichodesmium have attracted much attention in the research community ( 32 , 33 ). The presence of potentially denitrifying microorganisms associated with Trichodesmium has raised the hypothesis that Trichodesmium may even support denitrification in its O 2 microenvironment ( 34 ), as recently demonstrated experimentally in N 2 -fixing Nodularia colonies ( 21 ). In the latter study, it was shown that a complete aerobic and anaerobic N cycle can be present in the microenvironment of Nodularia colonies.…”
Section: Discussionmentioning
confidence: 97%
“…Trichodesmium are especially favored, and their large blooms are expected to further expand under future global warming scenarios because enhanced N 2 fixation was found to persist under high CO 2 irrespective of phosphorus limitation Walworth et al, 2018). Analogously to Nodularia blooms in the Baltic Sea (Wasmund, Nausch, & Voss, 2012), blooms of Trichodesmium in other marine systems develop seasonally in association with mixing of DIN-depleted but phosphorus-rich upwelling waters into warm, stratified oceanic waters that contain seed populations of Trichodesmium (Deutsch, Sarmiento, Sigman, Gruber, & Dunne, 2007;Hegde et al, 2008;Hood, Coles, & Capone, 2004).…”
Section: Planktonic Food Web Structure Across the Baltic Sea In Summermentioning
confidence: 99%
“…On the other hand, biogenic iron fertilization could have complementary effects on other aspects of nutrient limitation that ultimately affect the biological pump responsible for transport of carbon to the deep sea. It is known that Fe-limitation plays an important role in the capacity of diazotrophic cyanobacteria, for example Trichodesmium, to fix N 2 in the oligotrophic ocean (Walworth et al, 2018). Understanding how biogenic iron might affect diazotropy would be another area of useful research.…”
Section: Feasibilitymentioning
confidence: 99%